Particularities of hollow-core briquettes obtained out of spruce and oak wooden waste - Spirchez Cosmin; Lunguleasa Aurel; Matei Madalina (Revista Maderas-Ciencia Y Tecnologia, 2018)
Wooden hollow-core briquettes made of wooden waste represent an important category of wood-based combustible materials used in heating chambers. This paper aims to determine some of the characteristics of these briquettes made of spruce and oak waste. The comparison to the classic types of briquettes is made in order to identify the advantages and disadvantages of such briquettes. The main characteristics of these briquettes are presented, starting from size, density, abrasion, compression and ending with the inferior and superior calorific values, calorific density and ash content. The obtained results show that there are few differences between their characteristics and those of the classic ones. These differences depend on the pressing method and equipment, in comparison to other briquettes without a hollow core. Apart from the characteristics and the nature of the material being used, the hollow-core briquettes remain renewable combustible materials increasingly used in combustion (for heating purposes or in order to cook food or for heating in rural households or as substitutes for charcoal or cogenerate in various industrial fields). Given their economical character, there is complete suitability of these briquettes for cooking and heating.